Encountering the Other. André Scrima's Hermeneutics of Spiritual Hospitality - Tătaru-Cazaban, Bogdan (Religions, 2022)
A key figure in the ecumenical dialogue in the second half of the 20th Century, Fr André Scrima was also involved in the academic and interreligious life in Lebanon as a co-founder of the Institut d’Études Islamo-Chrétiennes at St.-Joseph Catholic University. In his courses, articles, and occasional papers, he developed a hermeneutical method to study the diversity of religious traditions, especially of the three Monotheisms, and to make possible the encounter with the religious otherness. This article aimed to shed light on hospitality as a hermeneutical category and spiritual practice in Scrima’s thought, having as a background Louis Massignon’s intellectual and mystical perspective on the relations between Christianity and Islam.